Review of the leafhopper genus Dryodurgades Zachvatkin (Hemiptera: Cicadellidae: Megophthalminae) with description of a new species from China - Zhang, Bin (Zootaxa, 2011)
The megophthalmine leafhopper genus Dryodurgades Zachvatkin is reviewed. One species is described as new, D. tortilis sp. nov., and three known species are recognized and illustrated. A key to Chinese species of Dryodurgades based on males is given and a checklist of all known species of Dryodurgades is also provided.